2017
DOI: 10.1515/msp-2017-0064
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations on the structural, spectroscopic, electronic and thermodynamic properties of (3-Oxo-3H-benzo[f]chromen-1yl) methyl N,N-dimethylcarbamodithioate-1ex

Abstract: Hartree-Fock and Density Functional Theory (B3LYP, B3PW91) calculations for the ground state of (3-Oxo-3H-benzo[f]chromen-1-yl) methyl N,N-dimethylcarbamodithioate have been presented and the calculated structural parameters and energetic properties have been compared with the available X-ray diffraction data. The vibrational frequencies have been calculated using optimized geometry of the molecule. The conformational properties of the molecule have been determined by computing molecular energy properties, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…is change is considered within the agreement between the theory and the experiment encountering the bulkiness of the molecule. Kara et al concluded that a 20 cm −1 difference between B3LYP and experimental for C�O for a relatively medium-sized molecule is a good agreement [32]. Atac et al suggested that the C�O difference between DFT and experimental can go up to 35 cm −1 differences [33].…”
Section: Discussionmentioning
confidence: 97%
“…is change is considered within the agreement between the theory and the experiment encountering the bulkiness of the molecule. Kara et al concluded that a 20 cm −1 difference between B3LYP and experimental for C�O for a relatively medium-sized molecule is a good agreement [32]. Atac et al suggested that the C�O difference between DFT and experimental can go up to 35 cm −1 differences [33].…”
Section: Discussionmentioning
confidence: 97%